THE PLAYFUL PHENOMENON IN THE LIFE OF TEACHERS OF PHYSICAL EDUCATION RESEARCHERS IN BODINESS (Fiep Bulletin - online, 2012)
Objective to socialize knowledge around the critical and creative game of the formation and life of professors of physical education. It explores the thematic ones of the playful one, the game, the aesthetic one and the corporality. The partners of the study are two professors whom the initial formation in Physical Education has. In synthesis of the conclusion we observe that the phenomenon of the playful in the life of the professors is a reality that appears for the presence of the game of the corporality, provoking expressive attitudes in daily making. Life histories had demonstrated that the processes of academic formation that had implied in a personal investment. The playful discloses the facet of learning to be and learning to coexist of these professors.
Keywords: Playful; Professional Formation; Life of Teacher